Tanggungjawaban Perusahaan yang Bergerak di Bidang Legal Consulting dalam Dimensi Nominee - Rismadewi, Avina (Acta Comitas : Jurnal Hukum Kenotariatan, 2019)
The offer of making Nominee Agreement services by legal consulting companies has an impact on the rapid development of nominee practices in Indonesia, whereas based on the provisions of Article 33 paragraph (1) and paragraph (2) prohibits Nominee Agreement in the ownership of shares in a company. This study aims to analyze the responsibilities of legal consulting companies that offer making Nominee Agarement online. This research uses normative legal research methods. The results of this study show that companies that deliberately offer Nominee Agreements violate the provisions contained in Article 33 paragraph (1) and paragraph (2), Law No. 25 of 2007, also violates the provisions of Article 9, Article 28 paragraph (1), and Article 36 of Law No. 11 of 2008, and may be subject to sanctions as referred to in Article 23 of Law No. 11 of 2008 and has responsibility to fulfill compensation as in the suit filed under Article 23 of Law No. 11 of 2008. Penawaran jasa pembuatan Nominee Agreement oleh perusahaan legal consulting berimbas pada berkembang pesatnya praktik nominee di Indonesia, sedangkan berdasarkan ketentuan Pasal 33 ayat (1) dan ayat (2) melarang Nominee Agreement dalam kepemilikan saham pada suatu perusahaan. Studi ini bertujuan untuk menganalisis tanggungjawab perusahaan legal consulting yang menawarkan pembuatan Nominee Agarement secara online. Penelitian ini menggunakan metode penelitian hukum normatif. Hasil dari studi ini menunjukan bahwa perusahaan yang dengan sengaja menawarkan Nominee Agreement melanggar ketentuan sebagaimana tercantum dalam Pasal 33 ayat (1) dan ayat (2), UU No. 25 Tahun 2007, juga melanggar ketentuan Pasal 9, Pasal 28 ayat (1), dan Pasal 36 UU No. 11 tahun 2008, dan dapat dikenakan sanksi sebagaimana dalam Pasal 23 UU No 11 tahun 2008 dan bertanggungjawab mengganti kerugian sebagaimana gugatan yang diajukan berdasarkan Pasal 23 UU No 11 tahun 2008.